2007
DOI: 10.1097/mlg.0b013e31813c14fc
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intraoperative Parathyroid Hormone Levels With Parathyroid Gland Size

Abstract: Preoperative serum calcium and baseline iPTH levels may be useful in predicting parathyroid adenoma weight and volume, respectively. Adenoma weight may relate to the percentage decrease of iPTH levels at the 10-minute postparathyroidectomy interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
3
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 9 publications
(23 reference statements)
6
33
3
6
Order By: Relevance
“…First, this study includes a substantially higher number of patients (n = 1235). Second, and similar to the findings of Moretz et al, 23 we did identify a highly significant correlation of both calcium levels and PTH levels with the gland weight. Finally, we used this correlation to create the WIN that capitalizes on this correlation to assist with intraoperative decision-making.…”
Section: Discussionsupporting
confidence: 88%
“…First, this study includes a substantially higher number of patients (n = 1235). Second, and similar to the findings of Moretz et al, 23 we did identify a highly significant correlation of both calcium levels and PTH levels with the gland weight. Finally, we used this correlation to create the WIN that capitalizes on this correlation to assist with intraoperative decision-making.…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to some studies, two studies have found a significant positive correlation between preoperative calcium levels and the weight of the adenomas 4 5. However, no correlation was found between the weight of the adenoma and the preoperative PTH contrary to the findings discussed in one of the studies published in the 1980 6.…”
Section: Discussionmentioning
confidence: 71%
“…To further stress the benefit of PTH in preoperative diagnosis, Robert et al suggested that a PTH level <4 times the upper limit of normal excludes a malignancy [4]. Other studies support the above trend—a recent case series looking at solitary adenomas causing asymptomatic disease have derived mean values of Preoperative PTH as 186 [5] and 165 ng/L [6], while research into carcinoma show higher PTH levels of 714 [2] and 1220 ng/L [7]. This consolidates the unusual nature of a PTH level of 3957 ng/L in an adenoma with no radiological, Intraoperative, or histological evidence of malignancy.…”
Section: Discussionmentioning
confidence: 99%